Dyrektor przedsiębiorstwa państwowego w okresie rządów autorytarnych - Siwik, Lidia (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In the paper the author demonstrates that the legally defined role of the state enterprise director reflected the highly politicized nature of this position within the context of authoritarian regimes from 1944 to 1989. This was particularly evident in the significant role that state enterprise directors played in shaping state policy. Authoritarianism manifested itself both on a microscale (in the internal relations between the enterprise director and employees) and on a macroscale (through the use of state enterprises managed by directors to exert broader influence on society). Consequently, the power of the state enterprise director was heavily conditioned by authoritarian governance systems, affecting the functioning of state enterprises and the politicization of economic development.
Keywords: dyrektor przedsiębiorstwa państwowego; przedsiębiorstwo państwowe; autorytaryzm w przedsiębiorstwach; władza autorytarna w przedsiębiorstwach państwowych